Reconstruction of General Education Policy in Universitas Muhammadiyah Yogyakarta - Sadam Fajar Shodiq; Abas Asyafah (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2020)
General education is not a merely portable decoration in university. In recent curriculum of general education, it has collectively played significant role in determining student’s success, achievement, retention and graduation. This research, then, aimed to know how far the implementation of MKDU (General education) policy in university, particularly in UMY. Technically, the research method employed in this research was descriptive-qualitative method, using data collection technique by in-depth interview, observation, and documentation. As a result, the findings of this research demonstrate that MKDU policy in UMY was as follows: (1) MKDU was under coordination of Vice Rector of Academic Affairs; (2) MKDU implementation was the responsibility of Head of Study Program respectively; (3) Credit of MKDU was regulated by Rector through Vice Rector of Academic Affairs; (4) Majority of MKDU lecturers was in accordance with their field; (5) MKDU development was performed via regular workshop in university; (6) Besides special courses, values of MKDU were taught in each subject course by sciences integrity